Physicochemical Characteristics and Antioxidant Activity of Rice Analog from Baruk Sago (Arenga microcarpha) and Purple Sweet Potatoes (Ipomea batatas L. Poiret) - Kaemba, Almawaty; Suryanto, Edi; Mamuaja, Christine F. (Jurnal Ilmu dan Teknologi Pangan, 2017)
Rice analog is an imitation of rice which made ingredients such as tubers and cereals that are similar in shape or nutrition composition as rice. The aim of this research was to physicochemical characteristic of rice analog from baruk sago and purple sweet potatoes, and to analyze antioxidant compound and its activity. The physical characteristic which evaluated as the color using color analyzer, although chemical characteristic includes moisture content, ash content, fat content, protein, fiber and carbohydrate using AOAC method. An antioxidant compound which evaluated was anthocyanin, and antioxidant activity was total antioxidant which evaluated using spectrophotometry. The result showed that rice analog which possesses concentration 65% was the best favorite level having good, aroma, taste and excelent texture using hedonic scales. Physical characteristic of rice analog color exhibit L 62,01, a* 12,49 dan b* 1,54. Rice analogue possesses chemical characteristic moisture content 7,99%, ash content 0,94%, fat content 0,81%, protein content 0,092%, fiber content 2,89%, and carbohydrate content 87,28%. Rice analogue possess anthocyanin 8,68 mg/L and exhibit total antioxidant 31,52 mg/mL. Physical characteristic of color from analog rice was less bright, and chemical characteristic was close to rice. Analog rice possess antioxidant compounds and show antioxidant activity.Â Keywords: anthocyanin, baruk sago, physicochemical, purple sweet potatoes, rice analog, total antioxidant